Variable Structures in the Stellar Wind of the Hmxb Vela X-1 - El Mellah, I (EDP Sciences, 2024)
Context. Strong stellar winds are an important feature in wind-accreting high-mass X-ray binary (HMXB) systems. Exploring their structure provides valuable insights into stellar evolution and their influence on surrounding environments. However, the long-term evolution and temporal variability of these wind structures are not fully understood. Aims. This work probes the archetypal wind-accreting HMXB Vela X-1 using the Monitor of All-sky X-ray Image (MAXI) instrument to study the orbit-to-orbit absorption variability in the 2-10 keV energy band across more than 14 years of observations. Additionally, the relationship between hardness ratio trends in different binary orbits and the spin state of the neutron star is investigated. Methods. We calculated X-ray hardness ratios to track absorption variability, comparing flux changes across various energy bands, as the effect of absorption on the flux is energy-dependent. We assessed variability by comparing the hardness ratio trends in our sample of binary orbits to the long-term averaged hardness ratio evolution derived from all available MAXI data. Results. Consistent with prior research, the long-term averaged hardness ratio evolution shows a stable pattern. However, the examination of individual binary orbits reveals a different hardness ratio evolution between consecutive orbits with no evident periodicity within the observed time span. We find that fewer than half of the inspected binary orbits align with the long-term averaged hardness evolution. Moreover, neutron star spin-up episodes exhibit more harder-than-average hardness trends compared to spin-down episodes, although their distributions overlap considerably. Conclusions. The long-term averaged hardness ratio dispersion and evolution are consistent with absorption column densities reported in literature from short observations, indicating that a heterogeneous wind structure - from accretion wakes to individual wind clumps - likely drives these variations. The variability observed from orbit to orbit suggests that pointed X-ray observations provide limited insights into the overall behaviour of the wind structure. Furthermore, the link between the spin state of the neutron star and the variability in orbit-to-orbit hardness trends highlights the impact of accretion processes on absorption. This connection suggests varying accretion states influenced by fluctuations in stellar wind density. © The Authors 2024.